2018
DOI: 10.1097/bot.0000000000001256
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Opioid Epidemic: Factors Predictive of Inpatient and Postdischarge Prescription Opioid Use After Orthopaedic Trauma

Abstract: Objective: The purpose of this study was to determine which factors influence inpatient and postdischarge opioid use after orthopaedic trauma. Design: Retrospective cohort study. Setting: Single Level 1 trauma center. Participants: The study included 235 adult trauma patients treated operatively for fracture with minimum 1 overnight hospital stay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…Among a population of patients who underwent shoulder arthroplasty, we found that preoperative opioid use increased the risk of postoperative opioid use and dependence. This is in concurrence with the hip and knee arthroplasty literature as well as those patients undergoing arthroscopic repairs 1 , 4 , 7 , 9 . It was also found that postoperative opioid use in these preoperative opioid-dependent patients continued even at 1-year follow-up (mean final follow-up of 47.1 months), indicating that patients who are opioid-dependent before shoulder arthroplasty remain chronically opioid-dependent even following surgery 4 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Among a population of patients who underwent shoulder arthroplasty, we found that preoperative opioid use increased the risk of postoperative opioid use and dependence. This is in concurrence with the hip and knee arthroplasty literature as well as those patients undergoing arthroscopic repairs 1 , 4 , 7 , 9 . It was also found that postoperative opioid use in these preoperative opioid-dependent patients continued even at 1-year follow-up (mean final follow-up of 47.1 months), indicating that patients who are opioid-dependent before shoulder arthroplasty remain chronically opioid-dependent even following surgery 4 .…”
Section: Discussionsupporting
confidence: 82%
“…Based on our results, patients undergoing RSA for RCA may be at the highest risk for postoperative opioid dependence. Perhaps we should limit postoperative prescriptions for these patients given recent studies among orthopedic trauma patients that found the opioid quantity dispensed at discharge after surgery is predictive of opioid use postoperatively 2 , 9 . The difference in opioid dependence rates is also important to note in that despite getting the same surgery, patients with preoperative OA require significantly less opioids than those with RCA.…”
Section: Discussionmentioning
confidence: 99%
“…Chi-square, Fisher exact, and Student t -tests, with Welch corrections in the setting of unequal variance, were generated in the appropriate setting. Because previous research has described a negative correlation between age and opioid use, 5 , 13 , 14 age-matched cohorts were derived from the larger groups for more equitable comparison. To age-match the groups, each cohort was subdivided into 10-year age categories (<21, 21 to 30, …, 61 to 70, 71+), and the youngest and oldest age groups were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have demonstrated that reducing opioid prescriptions may diminish long-term opioid use. 5 , 6 This, in combination with interventions such as increasing regional anesthesia use and providing nonopioid medications for pain control, has been advocated to reduce opioid dependence while providing acceptable analgesia. 7 - 9 …”
mentioning
confidence: 99%
“…A total of three studies looked at age and opioid prescription practices. 13,16,18 Fandino et al 18 found that younger age was associated with increased opioid prescription upon discharge for patients who underwent hip fracture fixation (p < 0.0001). In addition, younger patients were found to have increased discharge MME (p = 0.004).…”
Section: Pico 3: Opioid Prescription Patterns Between Age Cohortsmentioning
confidence: 99%